Philosophic premises of the social-and-legal government - Kusbekov, D.K. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article considers of scientific views and thinkers worldview since old orient and ancient culture. The author analyzes the social-and-legal issues in detail of government (state hood) along with the philosophical problem of the state. The author notes that he life’s origins of modern society begins with the mythical representation, which reflects the human’s first understanding his treatment to the world and the society. The author pointing out of the fundamental bases of state principles of social development regulation defines the urgency of the theme in the correspondence with interaction on the different period of human being and government.
Əлеуметтік-құқықтық мемлекеттің философиялық алғышарттары
Философские предпосылки социально-правового государства
Keywords: legal government (state hood); social and low; social and philosophic basis; world view of human (out look human)